Characterization of Musa paradisiaca L. Cellulosic Natural Fibers from Agro-discarded Blossom Petal Waste. Issue 11 (1st November 2020) - Prithivirajan, R.; Narayanasamy, P.; Al-Dhabi, Naif Abdullah; Balasundar, P.; Shyam Kumar, R.; Ponmurugan, K.; Ramkumar, T.; Senthil, S.
ABSTRACT: Musa paradisiaca: L. blossom petal (MPBP) fibers are extracted from banana plant agro-based domestic waste. The properties of MPBP fibers were reported for the first time in this communication. X-ray diffraction analysis showed the crystallinity index and size of 56.71% and 16.38 nm, respectively. The thermogravimetric analysis indicates that the MPBP fibers are thermally stable up to 220°C. Differential Scanning Calorimetry analysis gives two thermal degradation temperatures of 368.1 and 476.8°C with kinetic activation energy of 62.43 kJ. Tensile strength, Young's modulus, and strain at failure were determined from the single fiber tensile test as 108 MPa, 1.05 GPa, and 11.15%, respectively.